2020
DOI: 10.1139/cjfr-2019-0376
|View full text |Cite
|
Sign up to set email alerts
|

The level of relatedness affects self/nonself discrimination inEucalyptus urophyllaseedlings

Abstract: Plants can develop differentially because of their ability of self/nonself discrimination and the degree of kinship among them. Here, we evaluate the ability of self/nonself discrimination of Eucalyptus urophylla S.T. Blake roots in plant groups with different levels of relatedness. We used three plant groups: clonal, half-siblings, and population. Split-root plants were grown in pots containing either two roots of the same plant (SD) or of two different plants (NSD). The growth of root and leaves of the half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The related neighbourhood reduced the growth of the roots and above-ground parts, what has not been observed in unrelated neighbours. Bertoli et al (2020) demonstrated that the ability to recognise related plants exists when analysing eucalyptus (Eucalyptus urophylla; Myrtaceae) seedlings. They found an inverse relationship: competition with individuals from other populations or half-siblings limited growth but not the competition with clonal specimens.…”
Section: Interactions With Microorganismsmentioning
confidence: 99%
“…The related neighbourhood reduced the growth of the roots and above-ground parts, what has not been observed in unrelated neighbours. Bertoli et al (2020) demonstrated that the ability to recognise related plants exists when analysing eucalyptus (Eucalyptus urophylla; Myrtaceae) seedlings. They found an inverse relationship: competition with individuals from other populations or half-siblings limited growth but not the competition with clonal specimens.…”
Section: Interactions With Microorganismsmentioning
confidence: 99%